Management of the Integration of Kitab Kuning in PAI Teaching Materials: Optimization of the Sorogan and Bandongan Methods in Contemporary Madrasahs - Isnadia, Ririn; Safitri, Dinda Auliya; Neni (MANAGIERE: Journal of Islamic Educational Management, 2026)
This study analyzes the management of integrating Kitab Kuning into Islamic Religious Education (PAI) teaching materials through the optimization of the Sorogan and Bandongan methods in contemporary madrasas. The relevance of this study lies in the need for a systematic management model that bridges traditional pesantren pedagogies with modern curriculum demands. Using qualitative library research, this article examines the structural characteristics of Kitab Kuning and formulates a management framework for planning, organizing, implementing, and evaluating its integration within PAI learning. The findings show that Kitab Kuning remains a strategic source for strengthening students’ spiritual and conceptual understanding, yet its implementation requires structured management to adapt Sorogan into individualized assessment mechanisms and Bandongan into collective digital or classroom-based instruction. The proposed integration model supports curriculum enrichment, improves learning quality, and enhances teacher roles as knowledge transmitters. This study concludes that effective integration management strengthens both instructional depth and institutional identity in madrasas.